Diabetic Eye Disease From Therapeutic Pipeline to the Real World - Lo Giudice, Giuseppe (IntechOpen, 2022)
This book provides a comprehensive overview of current concepts in pathogenesis, diagnosis, and treatment of diabetic retinopathy. It is a collection of chapters written by experts that discuss advances in the understanding of pathophysiology, inflammatory and immunological factors and emerging concepts, clinical aspects, diagnostic management, and treatment strategies.